Pemberdayaan Masyarakat Berbasis Gerakan Literasi di Taman Baca Masyarakat Pondok Sinau Lentera Anak Nusantara - Hutri Agustino (Sospol : Jurnal Sosial Politik, 2019)
Empowerment derived from the word ‘power’. Therefore, the main idea of empowerment in contact with the concept of power. Meanwhile, the authority itself is often attributed with the ability to make other people do what we want, regardless of their wishes and interests. Empowerment refers to the ability of the people, especially the weak and vulnerable groups so that they have the ability in some respects. This in turn makes the praxis of empowerment of communities on the territory of the literacy movement. The inclusion of community empowerment on the literacy movement to make the movement experienced a transformation from the previous only general movement based on issues that are more specific, one that is in the Pondok Sinau Lentera Anak Nusantara as setting research. The purpose of this research is to know the realization community empowerment-based literacy movement and the impact of socio-economic change in the surrounding communities. By using the theory of community empowerment and literacy theory and qualitative descriptive method, it can be noted that there is a relationship between the empowerment of community-based literacy movement toward socio-economic changes in the surrounding communities. The background and the focus of community empowerment-based literacy movement in Pondok Sinau Lentera Anak Nusantara is as follows: (1) the existence of empowerment-based literacy movement in Pondok Sinau Lentera Anak Nusantara the answer to the problems of social-historical territory of the village; (2) the realization of the empowerment funded based on the principle of volunteerism and independence; (3) the main focus of the activities of empowerment is the transformation of the values of the characters building for the productive age group as well as encourage socio-economic independence based on a series of soft skill thematic activities.